2018
DOI: 10.1186/s12870-018-1340-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced phloem uptake of Myzus persicae on an aphid resistant pepper accession

Abstract: BackgroundThe green peach aphid (GPA), Myzus persicae, is economically one of the most threatening pests in pepper cultivation, which not only causes direct damage but also transmits many viruses. Breeding aphid resistant pepper varieties is a promising and environmentally friendly method to control aphid populations in the field and in the greenhouse. Until now, no strong sources of resistance against the GPA have been identified. Therefore the main aims of this study were to identify pepper materials with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 96 publications
0
67
1
1
Order By: Relevance
“…Sun and colleagues [247], screened 74 pepper accessions, belonging to C. annuum, C. frutescens, C. chinense and C. baccatum, for resistance to GPA. The authors identified three C. baccatum accessions with high (PB2013071) or intermediate resistance (PB2013062 and PB2012022) and elucidated possible mechanisms of aphid resistance.…”
Section: Aphidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun and colleagues [247], screened 74 pepper accessions, belonging to C. annuum, C. frutescens, C. chinense and C. baccatum, for resistance to GPA. The authors identified three C. baccatum accessions with high (PB2013071) or intermediate resistance (PB2013062 and PB2012022) and elucidated possible mechanisms of aphid resistance.…”
Section: Aphidsmentioning
confidence: 99%
“…The authors identified three C. baccatum accessions with high (PB2013071) or intermediate resistance (PB2013062 and PB2012022) and elucidated possible mechanisms of aphid resistance. The highly resistant genotype resulted in a severely reduced uptake of phloem, a significant callose deposition due to feeding of GPA, and in the accumulation of ROS (reactive oxygen species) [247].…”
Section: Aphidsmentioning
confidence: 99%
“…2). Several previous studies have shown that the reduced phloem sap ingestion from the host plants correlates with the enhanced resistance to daraju et al 2007;Koch et al 2015;George et al 2017;George and Lapointe 2018;Sun et al 2018). Besides the chemical substances present in the phloem sap of resistant plants, it is possible that the presence of morphological/physical barriers on host plants can also contribute to difficulties in stylet penetration and sustainment for sapsucking insect feeding (Baldin et al 2017;George et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…1 3 promising alternative. Resistance to aphids not only reduces the size of the aphid population on pepper (Frantz et al 2004;Sun et al 2018), but may also decrease the percentage of plants infected with viruses (Radcliffe and Ragsdale 2002). In several plant species, quantitative trait loci (QTLs) for resistance against aphids have been detected.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In a previous paper, we have described the screening and characterization of several sources of GPA resistance in Capsicum species (Sun et al 2018). Three accessions of Capsicum baccatum were shown to be resistant or intermediately resistant to GPA by negatively affecting aphid survival and reproduction.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%